Effects of γ-aminobutyric acid on the tissue structure, antioxidant activity, cell apoptosis, and cytokine contents of bursa of Fabricius in chicks under heat stress - Z. Chen; Y.-W. Zhou; C. Liang; Y.-Y. Jiang; L.-J. Xie (Archives Animal Breeding, 2016)
This study aims to investigate the changes in the tissue structure, cell apoptosis, antioxidant activity, and cytokine contents of the bursa of Fabricius (BF) in chicks under heat stress, and the regulation mechanism of the protective effect of dietary γ-aminobutyric acid (GABA) on BF in chicks. One-day-old male Wenchang chicks were randomly divided into a control group (CK), heat stress group (HS), and GABA + HS group. The index of BF, area of follicle, density of apoptosis, antioxidant activity (SOD, MDA, and GSH-PX), and cytokine contents (IL-1β, IL-6, TNF-α, and HSP70) in the BF tissue of chicks were determined at the end of week 1–6. Results showed that HS group had significantly decreased index of BF and area of follicle, and significantly increased density of apoptosis compared with CK group (P < 0.05), while GABA + HS group had significantly increased index of BF and area of follicle, and significantly decreased density of apoptosis compared with HS group (P < 0.05). There was no significant difference in the total SOD activity in the BF tissue among the three groups, except that GABA + HS group had an increase in total SOD activity in week 6, which was significantly different from that of CK and HS groups (P < 0.05). The GSH-PX activity in the BF tissue was high in all groups in the first 3 weeks, but decreased in week 4–6. The MDA content in the BF tissue of HS and GABA + HS groups was significantly increased compared with that of CK group (P < 0.05). There was no significant difference in the HSP70 content between HS and GABA + HS groups (P > 0.05), both of which were significantly decreased compared with that of CK group (P < 0.05). The contents of IL-1β, IL-6, and TNF-α in the BF tissue increased with age in all three groups in week 1–6. In the later BF development, the content of IL-1β in HS group was significantly decreased compared with that of CK group, whereas the content of IL-6 was significantly increased (P < 0.05), and no significant difference was observed in the content of TNF-α. In contrast, the content of IL-6 in GABA + HS group was significantly decreased compared with that of CK group, and the content of TNF-α was significantly increased (P < 0.05). These results suggested that heat stress caused structural damage to the BF tissue, increased cell apoptosis, and decreased antioxidant activity in the BF of chicks. GABA could alleviate the negative effects of heat stress on the BF tissue and improve the structural and functional development of BF in chicks, by increasing the antioxidant activity, down-regulating IL-6 content, and reducing cell apoptosis in the BF tissue of chicks.